Fetal striatal grafting slows motor and cognitive decline of Huntington's disease. Issue 9 (17th December 2013) - Paganini, Marco; Biggeri, Annibale; Romoli, Anna Maria; Mechi, Claudia; Ghelli, Elena; Berti, Valentina; Pradella, Silvia; Bucciantini, Sandra; Catelan, Dolores; Saccardi, Riccardo; Lombardini, Letizia; Mascalchi, Mario; et al.
Abstract : Objective: To assess the clinical effect of caudate-putaminal transplantation of fetal striatal tissue in Huntington's disease (HD). Methods: We carried out a follow-up study on 10 HD transplanted patients and 16 HD not-transplanted patients. All patients were evaluated with the Unified HD Rating Scale (UHDRS) whose change in motor, cognitive, behavioural and functional capacity total scores were considered as outcome measures. Grafted patients also received morphological and molecular neuroimaging. Results: Patients were followed-up from disease onset for a total of 309.3 person-years (minimum 5.3, median 11.2 years, maximum 21.6 years). UHDRS scores have been available since 2004 (median time of 5.7 years since onset, minimum zero, maximum 17.2 years). Median post-transplantation follow-up was 4.3 years, minimum 2.8, maximum 5.1 years. Adjusted post-transplantation motor score deterioration rate was reduced compared to the pretransplantation period, and to that of not-transplanted patients by 0.9 unit/years (95% CI 0.2 to 1.6). Cognitive score deterioration was reduced of 2.7 unit/years (95% CI 0.1 to 5.3). For grafted patients the 2-year post-transplantation [ 18 F]fluorodeoxyglucose positron emission tomography (PET) showed striatal/cortical metabolic increase compared to the presurgical evaluation; 4-year post-transplantation PET values were slightly decreased, but remained higher than preoperatively. [ 123 I]iodobenzamide single photon emission CT demonstrated an increase in striatal D2-receptor density during postgrafting follow-up. Conclusions: Grafted patients experienced a milder clinical course with less pronounced motor/cognitive decline and associated brain metabolism improvement. Life-time follow-up may ultimately clarify whether transplantation permanently modifies the natural course of the disease, allowing longer sojourn time at less severe clinical stage, and improvement of overall survival.